Fatal force-feeding or Gluttonous Gagging? The death of Kestrel SACHM 2575. (November 2015) - Ikram, Salima; Slabbert, Ruhan; Cornelius, Izak; du Plessis, Anton; Swanepoel, Liani Colette; Weber, Henry
Abstract: The use of digital CT imaging on a bird mummy from Iziko Museums of South Africa in Cape Town has allowed us to carry out a virtual autopsy on the animal. We have been able to establish its species, cause and probable time of death, as well as, for the first time, to find evidence for the maintenance of a captive raptor population in ancient Egypt. This may represent early evidence of keeping raptors in captivity anywhere in the world. Highlights: The genus and species of an animal mummy is established through CT imagery. A 3-D print of a skeleton within a wrapped package is made. The last meal(s) of a kestrel are identified. The cause of death of a kestrel mummy is identified. The possibility of breeding kestrels as offerings in ancient Egypt is explored.